2015
DOI: 10.1080/19317611.2015.1068902
|View full text |Cite
|
Sign up to set email alerts
|

Shame, Internalized Homonegativity, and Religiosity: A Comparison of the Stigmatization Associated with Minority Stress with Gay Men in Australia and Malaysia

Abstract: 2015): Shame, internalized homonegativity, and religiosity: A comparison of the stigmatization associated with minority stress with gay men in Australia AbstractIn this study we explore aspects of minority stress by comparing Malaysian (n = 234) andAustralian (n = 123) gay men on internalized homonegativity (IH) and internalized shame (IS) in a 2 x 2 multivariate analysis (country x relationship status). Religious motivation (RM) was also included as a variable due to the importance of religion in Malaysia as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Research has shown higher levels of internalized homonegativity in more conservative socio-cultural contexts and lower levels of sexual identity stigma in more inclusive sociocultural contexts (e.g., Brown et al, 2016;Herek et al, 2015;Riggle et al, 2017;Tran et al, 2018). Hence, a more comprehensive understating of sexual identity stigma and coming out of sexual minority men should examine socio-cultural differences, particularly in contexts typically underrepresented in the literature.…”
Section: Socio-cultural Differences In the Experiences Of Sexual Mino...mentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown higher levels of internalized homonegativity in more conservative socio-cultural contexts and lower levels of sexual identity stigma in more inclusive sociocultural contexts (e.g., Brown et al, 2016;Herek et al, 2015;Riggle et al, 2017;Tran et al, 2018). Hence, a more comprehensive understating of sexual identity stigma and coming out of sexual minority men should examine socio-cultural differences, particularly in contexts typically underrepresented in the literature.…”
Section: Socio-cultural Differences In the Experiences Of Sexual Mino...mentioning
confidence: 99%
“…Based on this reasoning, we expected heteronormative beliefs to be positively associated with internalized homonegativity (Hypothesis 2). However, heteronormative beliefs and internalized homonegativity differ between socio-cultural contexts (Brown et al, 2016;Riggle et al, 2017;Tran et al, 2018), such that Portugal has more inclusive social policies and laws than Turkey (e.g., Costa, 2021;European Commission, 2019;O'Neil & Çarkoğlu, 2020). As such, we expected heteronormative beliefs to have stronger positive associations with identity stigma (Hypothesis 3) and internalized homonegativity (Hypothesis 4) among Turkish (vs. Portuguese) sexual minority men.…”
Section: Overview and Hypothesesmentioning
confidence: 99%
“…Individuals who are uncomfortable with their sexual identity may also view their sexual attractions as unacceptable or feel shame about engaging in sexual activity that is representative of a personally unacceptable identity. Alternatively, those individuals with strong positive views of their sexual identity may report higher SS as a result of holding positive feelings regarding their sexuality (Brown, Low, Tai, & Tong, 2016).…”
Section: Additional Predictors Of Sexual Satisfactionmentioning
confidence: 99%
“…Also evident in a cross-cultural quantitative study of gay men in Australia and Malaysia, the researchers found that the latter group had a higher level of internalized homophobia. 22 This finding is perhaps unsurprising, given that Australia has legalized same-sex marriages and banned conversion practices in certain states, whereas these privileges were not enjoyed by Malaysian LGBTQ people. For researchers suggesting that LGBTQ people may wish to “return to normal life” due to internalized cisheterosexism, 11 psychologists should reflect on minority stress theory that elucidates internationalized cisheterosexism as a proximal stressor arising from distal stressors (eg, societal rejection of LGBTQ identity).…”
Section: Cisheterosexism In Malaysia: Debunking Misconceptionsmentioning
confidence: 99%